The inhibitory potential of Fc receptor homolog 4 on memory B cells - Götz R. A. Ehrhardt; Randall S. Davis; Joyce T. Hsu; Chuen‐Miin Leu; Annette Ehrhardt; Max D. Cooper (2003)
Fc receptor homolog 4 (FcRH4) is a B cell-specific member of the recently identified family of FcRHs whose intracellular domain contains three potential immunoreceptor tyrosine-based inhibitory motifs (ITIMs). The signaling potential of this receptor, shown here to be preferentially expressed by memory B cells, was compared with the inhibitory receptor FcγRIIb in B cells expressing either WT FcγRIIb or chimeric proteins in which the intracellular domain of FcRH4 was fused to the transmembrane and extracellular domains of FcγRIIb. Coligation of the FcγRIIb/FcRH4 chimeric protein with the B cell receptor (BCR) led to tyrosine phosphorylation of the two membrane-distal tyrosines and profound inhibition of BCR-mediated calcium mobilization, whole cell tyrosine phosphorylation, and mitogen-activated protein (MAP)-kinase activation. Mutational analysis of the FcRH4 cytoplasmic region indicated that the two membrane-distal ITIMs are essential for this inhibitory potential. Phosphopeptides corresponding to these ITIMs could bind the Src homology 2 (SH2) domain-containing tyrosine phosphatases SHP-1 and SHP-2, which associated with the WT FcRH4 and with mutants having inhibitory capability. These findings indicate the potential for FcRH4 to abort B cell receptor signaling by recruiting SHP-1 and SHP-2 to its two membrane distal ITIMs.